Literacy Innovation in Toilets: Integration of Discovery Learning Model for Early Childhood Education in Sikka, NTT - Boer, Alexius; Yufrinalis, Marianus; Dumbaris, Maximinus Adrianus Sarto; Maria, Sonya Kristiani; Gobang, Yonas Klemens Gregorius Dori (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2025)
This research is motivated by the learning conditions at the Early Childhood Education (ECE) level caused by several factors, namely the weak creativity of teachers in managing the classroom, the lack of media and learning support tools, and the low interest in learning from students. By describing innovations in the form of image design on the concept of Literacy Toilets, this study aims to explore the concept of Literacy Toilets initiated and collaborate with Discovery Learning learning steps. The research method applied is a qualitative research method with a descriptive analysis approach based on various information collected from observation studies, documentation and interview results with parties directly involved in education at the school. The results of the study show that the steps of the Discovery Learning model can be applied and collaborated with the school literacy movement through the concept of Literacy Toilets.Â  The application of the exploration method through the design of the Literacy Toilet can increase the Student Learning Activity (KBS) from 62.6% with the Medium category to 85.22% with the High category.